Grades, Aspirations, and Postsecondary Education Outcomes - Christofides, Louis N; Hoy, Michael; Milla, Joniada; Stengos, Thanasis (Canadian Journal of Higher Education, 2015)
In this paper, we exploit a rich longitudinal data set to explore the forces that, during high school, shape the development of aspirations to attend university and achieve academic success. We then investigate how these aspirations, along with grades and other variables, impact educational outcomes such as going to university and graduating. It turns out that parental expectations and peer factors have direct and indirect effects on educational outcomes through their impact on both grades and aspirations. Policy measures that enlighten parents about the value of education may positively modify educational outcomes.